Four-dimensional flow magnetic resonance imaging for noninvasive diagnosis of clinically significant portal hypertension and high-risk gastroesophageal varices in patients with cirrhosis - Jiachen Ji; Yi Xiang; Jinghui Dong; Hanyu Jiang; Tianyi Xia; Yunduo Li; Mengmeng Zhang; Changchun Liu; Xijun Gong; Bo Jin; Wen Shen; Gangfeng Zhu; et al. (EngMedicine)
Introduction: Noninvasive diagnoses of clinically significant portal hypertension (CSPH) and high-risk gastroesophageal varices are clinically relevant but challenging. Four-dimensional (4D) flow magnetic resonance imaging (MRI) provides comprehensive flow information and is a promising alternative. This study evaluated the efficacy of 4D flow MRI as a noninvasive method for diagnosing CSPH and high-risk varices in patients with liver cirrhosis. Methods: This prospective study enrolled consecutive patients diagnosed with liver cirrhosis at a tertiary referral center between October 2020 and March 2021. Each participant underwent abdominal 4D flow MRI. Hemodynamic parameters within the portal vein, including the average and peak flow velocities, normalized flow volume (Qnormal), and regurgitant fraction (R%), were extracted and compared between healthy individuals and patients with CSPH and between participants with high- and low-risk varices. Subsequently, these parameters were incorporated into a logistic regression (LR) model refined using L1 regularization and validated using five-fold cross-validation. The diagnostic efficacy was evaluated using receiver operating characteristic (ROC) curves. Results: Eighty-two participants were enrolled (71 patients diagnosed with liver cirrhosis and 11 healthy individuals serving as controls). Among hemodynamic parameters, patients with CSPH exhibited a notable increase in Qnormal of 0.66 ​± ​0.19 ​ml∗m2/[cycle∗kg] (P ​= ​0.001) and an R% of 1.98 (2.05) (P ​= ​0.002). Similarly, patients with high-risk varices showed a higher Qnormal of 0.61 ​± ​0.15 ​ml∗m2/[cycle∗kg] (P ​< ​0.001) and R% of 1.88 (2.81) (P ​= ​0.006). ROC analysis revealed an area under the curve (AUC) for Qnormal of 0.93 and 0.91 for R% for diagnosing CSPH, while the LR model showcased a superior AUC of 0.95. For high-risk varices, Qnormal and R% showed AUC values of 0.75 and 0.70, respectively, whereas the LR model showed a higher AUC of 0.84. Conclusion: As a noninvasive imaging modality, 4D flow MRI exhibits considerable potential for the diagnosis of CSPH and high-risk gastroesophageal varices; thus, it may minimize the reliance on invasive procedures in patients with cirrhosis.